Stone and stonemasons in Croatia - connecting people, communities and places - Lončar, Sanja, etnologinja (Array, 2014)
Stonemasonry plays an important role in the local communities in different parts of Croatia. It is associated with many aspects of inhabitants' everyday lives, having the key economic role as well as being the important factor in connecting with other communities and regions. In this paper I present the results of field studies from two Croatian regions – Croatian Littoral / Hrvatsko Primorje (Vinodol and Crikvenica) and Northern Dalmatia / Sjeverna Dalmacija (Ravni Kotari and Bukovica). I speak about masons and carvers from Vinodol and Crikvenica regions, who were, from the late 19th century until the 1970s, appreciated for their skills even outside their own regions. They had worked in other parts of Croatia and ex- Yugoslavia, as well as in other European and non- European countries. Their work has influenced the life in many places and regions, and stories about them are still present in the local communities of Vinodol and Crikvenica. Examples of Ravni kotari and Bukovica also show how stone and its treatment in the past has been an important factor in linking the regions and localities known for their skilled masons and carvers and stone processing (Podgorje ; Starigrad, Seline, Jesenice ; Benkovac, etc.). Here the stone and its treatment plays an important role in the life of contemporary inhabitants, which allows tracking of continuity and change conditioned by the social, cultural, technological and other contexts. The stonemasons' stories, as well as stories about them, suggest the possibilities and the need for further research on the role of stone and its treatment in local and regional communities and contexts.